Imparting Multifunctionality by Utilizing Biporosity in a Zirconium‐Based Metal–Organic Framework. Issue 6 (14th November 2019) - Jadhav, Ashwini; Gupta, Kriti; Ninawe, Pranay; Ballav, Nirmalya
Abstract: In this work, we have synthesized nanocomposites made up of a metal–organic framework (MOF) and conducting polymers by polymerization of specialty monomers such as pyrrole (Py) and 3, 4‐ethylenedioxythiophene (EDOT) in the voids of a stable and biporous Zr‐based MOF (UiO‐66 ). FTIR and Raman data confirmed the presence of polypyrrole (PPy ) and poly3, 4‐ethylenedioxythiophene (PEDOT ) in UiO‐66‐PPy and UiO‐66‐PEDOT nanocomposites, respectively, and PXRD data revealed successful retention of the structure of the MOF. HRTEM images showed successful incorporation of polymer fibers inside the voids of the framework. Owing to the intrinsic biporosity of UiO‐66, polymer chains were observed to selectively occupy only one of the voids. This resulted in a remarkable enhancement (million‐fold) of the electrical conductivity while the nanocomposites retain 60–70 % of the porosity of the original MOF. These semiconducting yet significantly porous MOF nanocomposite systems exhibited ultralow thermal conductivity. Enhanced electrical conductivity with lowered thermal conductivity could qualify such MOF nanocomposites for thermoelectric applications. Abstract : The biporous nature of UiO‐66 is utilized to incorporate conducting polymer moieties into the voids of the metal–organic framework. In this way the resulting nanocomposites display significant porosity and simultaneous million‐fold enhancement in electrical conductivity along with ultralow thermal conductivity.